Contribution écologique d’une espèce potentiellement invasive des Petites Antilles : Spathodea campanulata P. Beauv - Abati Yelji; Philippe Joseph; Yanis Jean-François; Kévine Baillard; Jean-Philippe Claude; Séverine Ely-Marius; Stéphane Sophie; Peguy Major (VertigO, 2023)
Trade across the globe has led to the introduction of plant and animal species into new territories. By crossing ecosystem barriers (environmental, reproductive and dispersal), some of them manage to become invasive. Spathodea campanulata, better known as the tulip tree is a species native to Africa introduced for ornamental purposes. It is a species that represents a great ecological threat; it has invaded the mesophilic secondary forests of the Pacific Islands (the Cook Islands, Fiji, French Polynesia, Guam, Hawaii, New Caledonia and Vanuatu) but also Puerto Rico, Brazil and Australia. In Martinique, the species has grown considerably in the natural environment. Once planted as an ornamental tree, the species now escapes from gardens and ornamental parks and gradually colonizes open plant formations. A floristic study on the Martinique territory allowed us to decipher the main life traits of Spathodea campanulata.